Can distance running determine the sex of your children? Can distance running determine the sex of your children?
Distance runners tend to have fewer male children, compared to the population at large. Author asks if distance running can determine the sex of your children. Result of studies: Mileage proved to be the only factor which had an impact on offspring gender, as running intensity (average training speed), overall life stress, paternal age, social status, manual vs. on-manual labour, competitive success, and the time interval between marriage and conception all had no significant effect. High-volume running tends to produce dips in testosterone, which in turn produces a decline in the output of boys (because of lowered testosteron levels). Higher training mileage levels of the mother should also drive female sex-hormone concentrations downward, increasing the chances of having a female.